2017
DOI: 10.1097/brs.0000000000002135
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Chewing Gum in Posterior Spinal Fusion Surgery for Adolescent Idiopathic Scoliosis

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…With the goal of blood loss minimization during spine surgery, we have concentrated our efforts toward developing a series of strategies that have resulted in nearly eliminating the need for blood transfusion. In contrast to some of the more recently published data regarding blood loss in surgery for AIS (Table 1) [13][14][15][16][17][18][19][20][21][22] our experience shows that blood transfusion was utilized in only one patient of a consecutive series of 130 cases of patients undergoing typical instrumented posterior fusion utilizing multiple pedicle screws and dual rod fixation. We conclude that the methods employed in both the surgical management and the anesthetic management of these patients had combined to allow this surgery to be performed with extremely low blood loss without any detectable adverse effects on the patient.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…With the goal of blood loss minimization during spine surgery, we have concentrated our efforts toward developing a series of strategies that have resulted in nearly eliminating the need for blood transfusion. In contrast to some of the more recently published data regarding blood loss in surgery for AIS (Table 1) [13][14][15][16][17][18][19][20][21][22] our experience shows that blood transfusion was utilized in only one patient of a consecutive series of 130 cases of patients undergoing typical instrumented posterior fusion utilizing multiple pedicle screws and dual rod fixation. We conclude that the methods employed in both the surgical management and the anesthetic management of these patients had combined to allow this surgery to be performed with extremely low blood loss without any detectable adverse effects on the patient.…”
Section: Discussioncontrasting
confidence: 78%
“…Spinal fusion for adolescent idiopathic scoliosis (AIS) is typically associated with high blood loss 1–22 . As a consequence, there are a number of articles proposing a variety of strategies to help minimize blood loss and the subsequent need for blood transfusion in scoliosis surgery.…”
mentioning
confidence: 99%
“…Needs to Explore an Effective Protocol for Prevent POI According to previous studies, preventive measures for POI include the early introduction of oral nutrition, early mobilization, use of coffee and chewing gum, [33][34][35][36][37][38] and treatments including appropriate fasting and intravenous fluid resuscitation, prokinetic agents, pantothenic acid, μ-receptor antagonist, and nasogastric decompression. 22,[39][40][41] However, the efficacy of these procedures remains controversial, and there is still a lack of a standardized protocol.…”
Section: The Association Between Sagittal Height Correction and Poimentioning
confidence: 99%
“…In terms of prevention, few studies assessing prophylactic medications showed their administration post-operatively to be inefficient in preventing post-operative ileus. 6 - 8 Analysis of risk factors found thoraco-lumbar fusion surgery, longer surgeries, higher intra-operative blood loss and higher postoperative morphine doses to be associated with post-operative ileus. 9 Nonetheless, given the clinical and economic significance of post-operative ileus, a more extensive risk factor analysis specifically to spine surgeries is still lacking.…”
Section: Introductionmentioning
confidence: 99%